المنتج المعماري الأكاديمي بين التصور الافتراضي والواقع التطبيقي -المباني التجارية الخدمية في مدينة اللاذقية مثالاً- - رنا غره (Tishreen University, 2016)
إنّ لمرحلة التعليم الجامعي الأكاديمي أهمية كبيرة بالنسبة للطالب الدارس لفن العمارة بكل أبعاده وتخصصاته ولعل من أبرزها هو التصميم المعماري، حيث تتنوع طبيعة المشاريع التي تطرح أمامه في سعي لتعريفه بأغلب الوظائف التي تشغلها المباني التي أوجدها الإنسان وواكبت تغيراتها ومستجداتها مسار تطوره واحتياجاته. لعل من أهم هذه المنشآت اليوم والتي بادر حقل التعليم المعماري في كلية الهندسة المعمارية بجامعة تشرين بطرح مسألة تصميمها بما يتوافق مع البيئة المكانية لمدينة اللاذقية وزمانها،هي المباني التجارية الخدمية، كونها بنى معمارية لاقت اهتماما ومطلباً ملحوظاً محلياً وعالمياً، تلبية لتطور سوق العمل ومستجدات الحياة اليومية المعاصرة، وذلك في ضوء الطريقة المتبعة في تعليم التصميم المعماري التي يسلط عليها البحث الضوء من خلال تحليل مجموعة من المشاريع التي قدمها الطلاب لتصميمها، لتقييم درجة توافقها مع روح العصر في مواكبة أهم ما يطرح في عالم العمارة عالميا من نظريات وأفكار ، ومع احتياجات المستخدمين المختلفة المحددة في نص المشروع المعطى من جهة، ومع الاشتراطات والأحكام التي نصت عليها أنظمة البناء في المدينة وفرضت واقعاً ميدانياً يتناوله البحث بكل أبعاده وجوانبه. Undergraduate academic education stage is of great importance for a student of architectural art in all its dimensions and specializations, the most important of which is architectural design, where the diverse nature of projects that are presented for him in a quest to identify most functions that human -made buildings occupy and these changes synchronized and updated the path of development and needs. Perhaps the commercial servicing buildings are the most important of these current facilities which the architectural education sector in the Faculty of architecture of the University. Because their are architectural structure that have met a distinguished attention and demand locally and internationally, to satisfy the improvement of labor market and the details of the daily modern life, in the light of the conducted methodology in teaching the "Architectural Design" course, which the research spots light on through the analysis of a group of projects that were designed by students, to evaluate its consistency with the essence of the period in follow up with the most important things that are presented in the field of architecture internationally of theories and ideas, and with the various needs of users that are identified in the contents of the project on one hand, and with the conditions and rules of building rules in the city which has imposed a current situation the research will study.